Characteristics of the grain and starch obtained from ecotypes of colored quinoa (Chenopodium quinoa Willd.) produced in the Peruvian highlands (Agroindustria, Sociedad y Ambiente, 2022)
Quinoa grains have high starch content, there are ecotypes that were not studied and these are becoming extinct, the objective was to evaluate the physical characteristics of three ecotypes of colored grains and evaluate yield, physicochemical characteristics and functional properties of starch; First, the physical characteristics of the grain were evaluated, then starch was extracted and yield, physicochemical characteristics of amylose and amylopectin by spectrophotometer and functional properties such as gelatinization temperature by thermometer, while swelling power, absorption capacity and solubility index were evaluated. They were evaluated at constant temperatures for 30 minutes, centrifuged and dried. It was found that the grains contain between 10,57 to 11,25% moisture, 2,31 to 2,86mm3 in volume, 1250 to 1253kg/m3 in density, 0,820 to 0,880mm in radius, and 280 to 347 grains per gram, while the hydrated grains showed a significant variation. Yields of 14,62 to 26,76%, 9,46 to 9,74% of amylose, 90,26 to 90,54% of amylopectin, 65,2 to 69,5°C of gelatinization temperature, 6,33 to 15,21 g/g swelling power, 1,24 to 4,02% water solubility index and 2,30 to 4,21 g/g water absorption capacity in the extracted starches. The quinoa studied has physical characteristics similar to other varieties and the functional properties of this starch are limited by the amylose content.
Keywords: starch, quinoa ecotypes; physical characteristics; physicochemical characteristics; functional properties.